Impacts and implications of oil palm on landscapes and livelihoods in Uganda’s Lake Victoria islands – an overview of recent research - The Green Livelihoods Alliance (Ecological Trends Alliance Texts, 2019)
The Government of Uganda had the best intentions when oil palm was established. The aim was to reduce poverty among the Lake Victoria island populations of Kalangala and Buvuma districts, and contribute to import substitution through domestic production of palm oil. The project established plantations in Kalangala in 2002 with crude palm oil production starting in 2010, and plantations will begin to be established in Buvuma from 2019. The benefits are readily reported by the main donor IFAD and the sole company BIDCO, part of Oil Palm Uganda Ltd. partly owned by Wilmar.